Scintigraphy of the hepatobiliar system in patients with pulmonary tuberculosis - Camargo, R. S. A.; Silva, E. T.; Griva, B. L.; Pereira, P. C. M. (Bmc, 2006)
The objective of this paper was to evaluate the hepatobiliary function of patients with pulmonary tuberculosis under triple treatment, using the technetium99m- DISIDA ( Tc-99m-DISIDA) hepatobiliary scintigraphy. Ten men and three women with pulmonary tuberculosis were subjected to hepatobiliary scintigraphy at the beginning of triple treatment (M1) and two months after it (M2). Patients were from the urban area, of low socioeconomic level, malnourished, and chronic alcohol and/or tobacco users. Ten normal individuals were evaluated as controls. Radiotracer images were acquired on a computerized gamma camera (Orbiter-Siemens) and T1/2 uptake and excretion values were calculated. Nutritional status and serum hepatic enzyme levels for each patient were evaluated at M1 and M2. None presented clinical or laboratory antecedent of hepatobiliary disease. At M1, there were no hepatic serum or kinetic alterations of the Tc-99m-DISIDA. At M2, patients presented better nutritional conditions than at M1; there was increased serum aspartate aminotransferase (AST) and reduced excretion time for 99mTc-DISIDA, which was interpreted as a more adaptive than toxic phenomenon, yet not all alterations were significant and none manifested clinically. Apparently, triple treatment acted on the liver inducing the P450 cytochrome enzymatic system, accelerating radiotracer excretion, which follows the same path as the bilirubins.
Keywords: pulmonar tuberculosis; scintigraphy; hepatobiliar system; antituberculosis drugs